Remdesivir therapy for severe pediatric COVID-19 in Singapore: a single-center retrospective observational cohort study - Seah, Valerie Xue Fen (2024)
There is a paucity of information on remdesivir (RDV) use in severe pediatric coronavirus disease 2019 (COVID-19). We aimed to explore the effectiveness of RDV as the cumulative proportion of pediatric COVID-19 patients deescalated from Day 5 of high dependency or intensive care unit (HD/ICU).